Microbial diversity of endolithic lichen-dominated communities in Victoria Land, Antarctica - Coleine, Claudia (Università degli studi della Tuscia - Viterbo, 2018)
Dottorato di ricerca in Ecologia e gestione sostenibile delle risorse ambientali Endolithic communities, the predominant life-form in the ice-free areas of Continental Antarctica, host among the most resistant and adapted microorganisms to extreme environmental pressure such as aridity, oligotrophy and low temperatures. Exploring these ecosystems at the edge of life may be relevant for monitoring and predict the effects of climate change; besides, our knowledge on microbial diversity and composition is still limited. This study explored the microbial diversity in the lichen-dominated communities of Victoria Land, visited during the XXVI Italian Expedition (2010-2011). First, DGGE was performed on different types of rocks (quartz, dolerite, sandstone and granite) and then metabarcoding was implemented on a selection of sandstone samples, the best rock substratum for microbial colonization. We have also performed the whole-genome sequencing analysis on seven endolithic fungi to make comparative genomics. Overall, our findings indicated arelatively low bacterial and fungal species diversity, compared with microbial communities inhabiting temperate areas. The evenness of the communities indicated a very high degree of specialization with a consequent low resilience; therefore, any possible perturbation may lead to irreversible consequences. We also demonstrated that altitude and sea distance did not influence the biodiversity, concluding that other environmental parameters (e.g. North/South exposure) should be considered in a next sampling as potential driving factors for communities composition. This work represents the widest molecular survey to date and the first wide window on the actual biodiversity and composition of the Antarctic endolithic communities. Le comunità endolitiche rappresentano la forma di vita predominante nelle aree deglaciate dell'Antartide Continentale e sono note per ospitare microrganismi tra i più resistenti ed adattati a forti pressioni ambientali, ad esempio aridità, oligotrofia, basse temperature ed irraggiamento UV. La nostra conoscenza sulla composizione microbica delle comunità endolitiche antartiche è ancora scarsa. In questa tesi si analizza la biodiversità nelle comunità endolitiche dominate dai licheni nella Terra Vittoria (Antartide Continentale) su campioni raccolti durante la XXVI Spedizione Italiana (2010-2011). È stata inizialmente eseguita la tecnica DGGE su diversi tipi di rocce (quarzo, dolerite, arenaria e granito) ed una selezione di roccia arenaria è stata sottoposta a metabarcoding. Inoltre è stato sequenziato l’intero genoma di sette funghi isolati da queste comunità per studi di genomica comparativa. I nostri risultati indicano una bassa diversità batterica e fungina, rispetto a comunità microbiche in climi temperati. Le curve di Pareto-Lorenz mostrano un alto grado di specializzazione ed una bassa resilienza, suggerendo che qualsiasi perturbazione esterna può portare a conseguenze irreversibili sull’equilibrio della comunità. Inoltre, si è visto che le variabili ambientali altitudine e distanza del mare non influenzano la biodiversità ed ulteriori parametri abiotici (ad esempio l'esposizione solare) potrebbero svolgere un ruolo chiave nello sviluppo e distribuzione delle comunità endolitiche antartiche. I dati ottenuti rappresentano un contributo importante per pianificare un campionamento più mirato nelle prossime campagne, al fine di comprendere come questi ecosistemi possano essere influenzati dai cambiamenti climatici.